Dietary proclivities of Paranthropus robustus from Swartkrans, South Africa - L’Engle Williams, Frank (Anthropological Review, 2015)
Pleistocene Paranthropus robustus fossils from Swartkrans have yielded stable isotope values suggesting some foraging on C4 plants possibly including underground storage organs. Dental microwear texture analysis on P. robustus (SK 6, SK 34 and SK 47) from Swartkrans Member 1 is performed to examine whether tooth surface damage from mastication agrees with prior dietary inferences from carbon isotopes. There is considerable variation in textural characteristics among the P. robustus specimens. Specifically, adult SK 34 stands apart from the two subadult specimens, SK 6 and SK 47, suggesting life history could be reflected in patterns of dental microwear texture characteristics, although seasonality and availability of fallback foods may also explain the variation observed in P. robustus. The fossils all exhibit elevated surface texture complexity, resembling the values for Lophocebus albigena and Cebus apella, and to a lesser extent, Pan troglodytes. Paranthropus robustus is dissimilar to primary folivores, such as Trachypithecus cristatus or folivore-frugivores such as Alouatta palliata suggesting leaves comprised very little of its diet. The textural fill volume of P. robustus differs from that observed in extant primates from tropical forests indicating extreme durophagy, perhaps a function of differences in habitat. Ingestion of extraneous grit on the underground parts of plants and from terrestrial resources, perhaps as fallback foods or as dietary staples, may account for these enamel textural properties and may help explain the mixed C3/C4 isotopic signal in P. robustus.